The Impact of Culture on Brand Extension: The Specific Versus Diffuse Dimension and Product Category Similarity - Branch, John D; Dalmia, Maansi; Mo, Ethan (Journal of Marketing Development and Competitiveness, 2022)
In this research, we explored whether or not cultural differences can explain the differences in acceptance of brand-extended products across different societies. Specifically, we hypothesised that a society’s degree on Trompenaars’ specific versus diffuse continuum might explain the acceptance or rejection of brandextended products in dissimilar product categories. We tested our hypothesis in two separate studies— one which is based on the number of products which are marketed by five global companies in six countries, and another which is based on the number of product categories in which 250 companies market products in five countries. Both studies support the hypothesis, and buttress the general claim that culture still matters.